PENINGKATKAN KEMAMPUAN BELAJAR MATEMATIKA SISWA MELALUI PENGGUNAAN MODELTHINK PAIR SHARE (TPS) - Asih, Sri (STKIP PGRI Tulungagung, 2018)
This research is aimedÂ to improve mathematics students learning ability in elementary school, especially on fraction materials through throughthe implementation of cooperative learning on think pair share. This research was a classroom action research refferedto Kemmis and Mc Taggartâ??s design, which includes planning, acting, observing, and reflecting. The research subject were all the student of sixthgrade Â in SDN 2 Tropodo Waru Sidoarjo inÂ theÂ the period of 2015/2016. Before the implementation of the action, the ability of learn to mathematics very low and the student less enthusiastic for mathematics class. After the action is applied, the results of the test and ability learn to mathematics onÂ cycle I and cycle II, there is a significant increase.Â Keywords: mathematics learning ability, TPS